Assessing The Role Of Environmental Innovation, Credit Access, And Governance In Shaping The Financial Sustainability Of Indonesian MSMEs - Helmina Br Ginting; Syamsu Rijal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study looks into how Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia interact with environmental innovation, governance, credit availability, and financial sustainability. Data were gathered from 145 MSMEs working in different industries through the use of a quantitative technique. The proposed relationships were tested using Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis. The findings show that among Indonesian MSMEs, financial sustainability is positively impacted by environmental innovation, loan availability, and governance. In particular, environmental innovation has become a major force behind financial sustainability, emphasizing how crucial it is to implement eco-friendly methods. Financial sustainability was also found to be positively impacted by enhanced loan availability and robust governance frameworks, highlighting the necessity of encouraging regulatory environments and financial resources for MSME development. Mediation analysis revealed intricate correlations between the variables, clarifying indirect effects further. Policymakers, practitioners, and MSME stakeholders can benefit from these findings, which highlight the significance of holistic approaches to MSME development and offer strategies for improving financial sustainability and resilience